Young bumiputera entrepreneurship programme / Suzaina Ismail - Ismail, Suzaina (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
TUBE (Young Bumiputera Entrepreneurship Programme) is one of the government’s initiatives which is aimed to assist youths who would venture into business and to encourage them to contribute to the nation. Therefore, it has become a launching pad for aspiring young entrepreneurs. UiTM Perak Branch was invited to conduct the second phase of TUBE, in collaboration with SME Corp and Universiti Kebang-saan Malaysia this year. The programme was held from 16 to 28 March 2018 at PLKN Camp, Kota Lama, Kuala Kangsar and was attended by 100 Perak youths.